Vinculin phosphorylation at residues Y100 and Y1065 is required for cellular force transmission. - Auernheimer, Vera; Lautscham, Lena; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Fabry, Ben; Goldmann, Wolfgang (Journal of cell science, 2015)
The focal adhesion protein vinculin connects the actin cytoskeleton via talin and integrin with the extracellular matrix. Vinculin consists of a globular head and tail domain, which undergo conformational changes from a closed auto-inhibited conformation in the cytoplasm to an open conformation in focal adhesions. Src-phosphorylation has been suggested to regulate this conformational switch. To explore the role of phosphorylation in vinculin activation, we used knock-out mouse embryonic fibroblasts re-expressing different vinculin mutants in traction microscopy, magnetic tweezer microrheology, FRAP, and actin-binding assays. Compared to cells expressing wildtype or constitutively active vinculin, we found reduced tractions, cytoskeletal stiffness, adhesion strength, and increased vinculin dynamics in cells expressing constitutively inactive vinculin or vinculin where Src-phosphorylation was blocked by replacing tyrosine at position 100 and/or 1065 with non-phosphorylatable phenylalanine. Replacing tyrosines with phospho-mimicking glutamic acid restored cellular tractions, stiffness, adhesion strength as well as vinculin dynamics, and facilitated vinculin-actin binding. These data demonstrate that Src-phosphorylation is necessary for vinculin activation, and that phosphorylation controls cytoskeletal mechanics by regulating force transmission between the actin cytoskeleton and focal adhesion proteins.